Changes in phytoplankton communities in arsenic contaminated waters at the Ron Phibun district of Nakhon Si Thammarat Province - Weeradej Meeinkuirt (Prince of Songkla University, 2008)
Thesis (M.Sc., Ecology)--Prince of Songkla University, 2008